Implementation of the Affirmation School Operational Cost Policy at SMP Negeri 3 Suluun Tareran, South Minahasa - Runtuwene, Noldy Nofri; Mandagi, Marthinus; Dilapanga, Abdul Rahman (Technium Social Sciences Journal, 2022)
This study describes Affirmation School Operational Costs or Bantuan Operasional Sekolah (BOS) Policy management in South Minahasa District Study at SMP Negeri 3 Suluun Tareran. This study uses qualitative research methods and data collection techniques: Observation, Interview, and Documentation. The primary data source of this research is the Affirmation of School Operational Costs (BOS) Policy in the South Minahasa Regency. In this case, the Policy on Management, Reporting, Responsibility for the Use of Funds and Distribution of Funds by the School BOS Team in South Minahasa Regency Study SMP Negeri 3 Suluun Tareran and Secondary data sources are supporting documents, archives, and literature. The results showed that: Policies in managing, reporting, responsible for the use of funds, and distribution of funds by the School BOS team are still very lacking and are spent by the policies contained in the Minister of Education and Culture Number 24 of 2020 It has not been implemented optimally even though the document data component of the use of funds and expenditures has been fulfilled, but its use in schools is still inadequate and has not been implemented optimally because of the lack of human resources and the internet network of Telkomsel and others has not yet entered the SMP Negeri 3 Suluun school. The results of the study concluded: (1) Affirmation School Operational Cost (BOS) Policy in South Minahasa Regency. In this case, the Policy on Management, Reporting, Responsibility for the Use of Funds and Distribution of Funds by the School BOS Team as an adequate policy in the use of Affirmation BOS funds and must be improved with other supporters such as adequate human resources and can work together with the Regency BOS Team in the process of using Affirmation BOS funds so that their use in schools can be carried out and on target; (2) Administrative Management of the Use of Affirmation BOS Funds is entirely assisted by the Regulation of the Minister of Education and Culture Number 24 of 2020. However, the use of fund expenditures is still inadequate with the condition of the school and the school environment, especially human resources which are the motivation in the teaching and learning process. For this reason, schools must have their policies so that their use can be by the conditions and the school environment.